Franchisee failures in Malaysia: Contribution of financial and non-financial factors - Mohd Harif, Mohd Amy Azhar; Chee, Hee Hoe; Mahad Noor, Norsyema Hani (World Business Institute, Australia, 2011)
This paper reports on the exploratory study on Malaysian franchisees who have failed in their franchise business. A stratified purposive sampling frame was used in which all the five failed franchisees who have registered with the Registrar of Franchise (ROF) were selected for this study. In-depth telephone interviews were carried out.The interview was a semi-structured open-ended format questions which has been formulated based on the franchising research literature in which 13 factors have been identified as contributing to the franchisee failure.These 13 factors can be categorized into two categories, non-financial and financial factors. The non-financial factors consisted of nine factors and financial factors consisted of four factors. The non-financial factors include too rapid expansion of the franchise business, greed of franchisee, franchisee attitude, poor service, poor management of the franchise business, conflict with franchisor, legal imperfection, location and external factor. The financial factors include under capitalization of the franchisee, high overhead expenses, cash flow mismanagement and bad payers’ franchisee. This paper provides evidence that the 13 factors linked with franchisee failure also contributed to franchisee failures in Malaysia.